Better Students Ask More Questions.
A reaction has a forward rate constant of 2.3 × 10^6s–1 and an equilibrium...
1 Answer | add yours
You need to use the following equilibrium ratio to evaluate the rate constant for the reverse reaction, such that:
`K = (K_f)/(K_r)`
`K_f` represents the rate constant of forward reaction
`K_r` represents the rate constant of reverse reaction
Since the problem provides the equilibrium constant and the rate costant of forward reaction, you need to replace the given values in equation above, such that:
`4.0 × 10^8 = (2.3 × 10^6)/(K_r) => K_r = (2.3 × 10^6)/(4.0 × 10^8)`
`K_r = 0.575 x 10^(6 - 8)`
`K_r = 0.575 x 10^(-2)`
Hence, evaluating the rate constant of reverse reaction, under the given conditions, yields `K_r = 0.575 x 10^(-2).`
Posted by sciencesolve on June 22, 2013 at 4:49 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.